Perceived work stressors and the transition to burnout among nurses in response to the pandemic: implications for healthcare organizations - Emanuele Maria Giusti; Marco Mario Ferrario; Giovanni Veronesi; Alessia D'Amato; Francesco Gianfagna; Licia Iacoviello (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVES: This study aimed to assess the associations of pre-pandemic perceived work stressors and work satisfaction among nurses, including nurse assistants, with burnout profiles and their transitions in response to the pandemic. METHODS: Three hundred and thirty-seven nurses working in an Italian University hospital participated in a longitudinal study including a survey in August 2019 investigating perceived work stressors (assessed using the HSE Indicator Tool), work satisfaction (Work Satisfaction Scale), and burnout (Maslach Burnout Inventory), and a second survey in December 2020 assessing burnout. Using latent transition analysis, we identified burnout profiles and then estimated the associations between work stressors and satisfaction on profiles and transitions. RESULTS: We identified three pre-pandemic profiles, namely engaged (67%), ineffective (15%), and burnout (18%); and three pandemic profiles, namely engaged (37%), exhausted (51%), and severe burnout (12%). The severe burnout profile consisted of 70% nurses classified in the burnout profile before the pandemic. Overall, work stressors and satisfaction were associated with both pre-pandemic and pandemic burnout profiles. Among nurses not in the burnout profile prior to COVID-19, pre-pandemic hostile relationships increased [odds ratio (OR) 1.19, 95% confidence interval (CI) 1.05-1.34] and work satisfaction decreased (OR 0.82, 95% CI 0.68-0.98) the probability to transition to exhausted. Moreover, work satisfaction (OR 0.54, 95% CI 0.32-0.91) and participation in work organization (OR 0.69, 95% CI 0.51-0.93) protected from transitioning to severe burnout. The association between peer support and the transition to exhausted needs further investigation. CONCLUSIONS: Pre-pandemic work stressors and satisfaction were associated with pandemic burnout and burnout transitions. To enhance preparedness for future crises, healthcare managers should carefully assess and tackle work-related constraints affecting nurses.